Radiation dose reduction method combining the ECG-Edit function and high helical pitch in retrospectively-gated CT angiography. Issue 3 (August 2022) - Masuda, T.; Funama, Y.; Nakaura, T.; Sato, T.; Okimoto, T.; Gotanda, R.; Arao, K.; Imaizumi, H.; Arao, S.; Ono, A.; Hiratsuka, J.; Awai, K.
Abstract: Introduction: The purpose of this study was to demonstrate that dose reduction does not compromise image quality when combining high helical pitch (HP) and the ECG-Edit function during low HP retrospectively gated computed tomography angiography (CTA). Methods: This study made use of a pulsating cardiac phantom (ALPHA 1 VTPC). The heart rate (HR) of the cardiac phantom was changed in five intervals, every 5 beats per minute (bpm), from 40 to 60 bpm. Evaluation of a range of HR was important because data loss might occur when combining a low HR and high HP. We performed retrospectively gated CTA scans five times using a low HP (0.16) and high HP (0.24), for each of the five HR intervals, using a 64-detector row CT scanner. The CT volume dose index (CTDIvol ) was recorded from the CT console of each scan. For the images with data loss, data were repaired using the ECG-Edit function. We compared the CTDIvol, estimated cardiac phantom volume, and the visualization of the coronary ladder phantom between HP 0.16, with or without repaired HP 0.24, using the ECG-Edit function. Results: Data loss occurred with a HR of 40 bpm and 45 bpm when using HP 0.24. The CTDIvol was reduced by approximately 33% with HP 0.24 when compared with HP 0.16. There were no significant differences in the mean cardiac motion phantom volume and visualization scores between HP 0.16 and with and without repaired HP 0.24 using the ECG-Edit function (p < 0.05). Conclusion: The ECG-Edit function is potential useful for repairing the lost data in patients with a low HR, and when combined with a high HP, it is possible to reduce the radiation dose by approximately 33%. Implications for practice: The ECG-Edit function and high HP may be a viable option in pediatric CTA studies.